Analysis of Service Quality and Coverage Based on LoRaWAN Network: A Case Study of Air Quality Monitoring in Grand Depok City - Pratama, Legenda Prameswono; Syaifudin, Ahmad Ragil (Department of Electrical Engineering, 2025)
Smart living is an evolution of the Internet of Things (IoT). The concept of smart living itself refers to the ability to control and connect everything in the surrounding environment to the Internet. The research method used in this study is observational, focusing on the range of LoRa usage with parameters including Receive Signal Strength Indicator (RSSI) and Signal to Noise Ratio (SNR). The study results show that the average RSSI is -94.6 dBm at 50 meters, -105.4 dBm at 100 meters, -106.8 dBm at 150 meters, -111 dBm at 200 meters, -106.6 dBm at 250 meters, and -108.8 dBm at 300 meters. Meanwhile, the highest SNR value was recorded at 50 meters with 11 dB, while the lowest was at 300 meters with -8 dB. The highest error rate was observed at 250 meters, with an error value of 88%. Lack of error value indicates that as the distance between the transmitter and receiver increases, the signal's strength and quality tend to decrease, ultimately affecting communication reliability. Noise becomes more dominant at greater distances than the received signal.